SECURING THE DIGITAL NATION: A RESEARCH EXPLORATION OF CYBERSECURITY IN E-GOVERNMENT - Dyah Rahayuning Perwitasari; Perdana, Gusti Naufal Rizky; Lestari, Lara Ayu; Zana, Iqbal Saputra; Bato, Bulan Erika (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study examines the development and trends in cybersecurity research within the context of e-government from 2012 to 2024 using a bibliometric analysis method. Through bibliometric analysis, this research analyzes publications indexed in the Scopus database to identify trends, author contributions, institutions, and countries involved in cybersecurity research in the digital government sector. The analysis results indicate that cybersecurity topics in e-government have gained increasing attention in line with the growing adoption of digital technologies in government. Dominant themes such as cybersecurity, security, system, technologies, digital, and e-government reflect efforts to enhance government efficiency and transparency while addressing cybersecurity challenges. Furthermore, the study identifies the growing importance of implementing technical solutions such as blockchain and artificial intelligence (AI) to strengthen the security of digital government systems. The research also highlights significant contributions from specific authors, institutions, and countries in enriching this body of literature. Nonetheless, this study is limited by the scope of data used and proposes future research directions that incorporate socio-political factors and emerging technologies to reinforce the secure implementation of e-government.